Liberdade religiosa e segurança internacional: desafios e perspectivas - Lima, Clarisse Laupman Ferraz (2016)
The objective of the present study is to analyse the observance of religious freedom as it pertains to the current international security situation around the world. Recognizing the fact that historically, religion and law coexisted along a fine line. Religions have been responsible for the power construction of relationships throughout human history. It is considered within the international panorama that the topic of religious freedom and the need for security threaten each other boundaries. Terrorism has brought fear and the need for security. The question to tackle is how much freedom is humanity to lose in the name of security. This study will be disseminated in three parts. First, it examines the problematic relationship between religion and political power, in regards to religious people. Secondly, the theoretical and doctrinal aspects are presented as relevant to the construction of religious freedom, highlighted by a Laicity, and the formation of international security. Finally, in the third part, investigates the challenges and perspectives between o religious freedom and the need for security in the current world. This work seeks to demonstrate that religious freedom was a determinant achievement of international law, and this law should not be revoke dues to the fear currently prevalent in world. We envisage an international collective action paragraph perpetuate the idea of religious freedom and security are parts for the ear gear, working of the greater purpose: world peace